2016
DOI: 10.1371/journal.pone.0155321
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Screening of Native Scenedesmus sp. Isolates Suitable for Biofuel Feedstock

Abstract: In current study isolates of two native microalgae species were screened on the basis of growth kinetics and lipid accumulation potential. On the basis of data obtained on growth parameters and lipid accumulation, it is concluded that Scenedesmus dimorphus has better potential as biofuel feedstock. Two of the isolates of Scenedesmus dimorphus performed better than other isolates with respect to important growth parameters with lipid content of ~30% of dry biomass. Scenedesmus dimorphus was found to be more sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 39 publications
5
20
0
2
Order By: Relevance
“…Other than hydrocarbons, a high percentage of fatty acids (61.44%) was also recorded, major fatty acid recorded were C19:1, C19:2 and C19:3, which were methyl hexadecanoate (palmitate) (30.20%), methyl 9, 12, 15-octadecatrienoate (linolenate) (11.03%), methyl octadecaenoate (elaidate) (8.74%), methyl 9, 12-octadecadienoate (linolenate) (7.51%) and methyl 5, 9, 12-octadecatrienoate (gamma-linolenoate) (2.07%) (Tables 5 and 6). In support of our isolated potent microalgal isolate Chlorella fw-12, a recent study has shown that other green algae Scenedesmus dimorphus performed better than other isolates with respect to important growth parameters and lipid content of near about 30% of dry biomass (Gour et al, (2016). Selvarajan et al, (2015) reported 42.1% ± 2.5% (of dry biomass) of lipid in case of Chlorella vulgaris.…”
Section: Microalgaesupporting
confidence: 71%
“…Other than hydrocarbons, a high percentage of fatty acids (61.44%) was also recorded, major fatty acid recorded were C19:1, C19:2 and C19:3, which were methyl hexadecanoate (palmitate) (30.20%), methyl 9, 12, 15-octadecatrienoate (linolenate) (11.03%), methyl octadecaenoate (elaidate) (8.74%), methyl 9, 12-octadecadienoate (linolenate) (7.51%) and methyl 5, 9, 12-octadecatrienoate (gamma-linolenoate) (2.07%) (Tables 5 and 6). In support of our isolated potent microalgal isolate Chlorella fw-12, a recent study has shown that other green algae Scenedesmus dimorphus performed better than other isolates with respect to important growth parameters and lipid content of near about 30% of dry biomass (Gour et al, (2016). Selvarajan et al, (2015) reported 42.1% ± 2.5% (of dry biomass) of lipid in case of Chlorella vulgaris.…”
Section: Microalgaesupporting
confidence: 71%
“…Furthermore, microalgae represent an alternative energy resource to non-renewable energy coming from fossil fuels (Makarevicien_ e et al 2011;Gour et al 2016). The importance of microalgae as an energy resource lies in the world's high energy demand which leads to the depletion of traditional energy resources such as fossil fuels which are associated with the release of harmful gases such as nitrogen oxide, carbon dioxide, carbon monoxide, and sulphur oxide into the atmosphere (Ren 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Scenedesmus dimorphus performed better than the other 2 species on all media tested, which once again proves its superiority. 13 Selection of an optimal culture medium will be a key factor in exploiting the potential of microalgae for lipid and bioactive compound production. Given the diverse nature of microalgae species, no single medium would be suitable for higher growth and production in all the species, so it is worth trying a few different formulations that are frequently used and found in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Then,the cell pellets were freeze-dried and lyophilized (New Brunswick, NJ, USA). The dry weight of the microalgal biomass was determined by the gravimetrical method, 13 and the biomass growth was represented in terms of dry weight (g L −1 ). Biomass productivity (Pdwt) was expressed as the dry biomass produced in grams per liter per day (g L −1 day −1 ).…”
Section: Methodsmentioning
confidence: 99%